Hubungan antara Faktor Klinikohistopatologi dan Kualitas Hidup Pasien Kanker Endometrium Pasca Operasi di RSUP Dr.Sardjito Yogyakarta Menggunakan Modul Kuesioner EORTC QLQ-C30 dan EN 24 - Dini Mahrani; Ahsanudin Attamimi; Ardhanu Kusumanto (JURNAL KESEHATAN REPRODUKSI, 2021)
Background: According to data from the "Endometrial Cancer Report" by the World Cancer Research Fund and the American Institute for Cancer Research (WCRFI), endometrial cancer is the sixth most common malignancy in the world and is the largest cancer in female organs, after cervical cancer. This incidence is increasing every year, it is predicted to increase about 5% of new cases each year. The main prognostic factors of endometrial cancer are determined by the histological type, stage, degree, differentiation of the tumor, invasive myometrial level and increase in lympho-vascular invasion. In addition to determining the histopathological factors, the prognosis is also determined from the clinical patient. Several studies have shown certain clinical factors also improve the condition and prognosis of the disease. Prognosis of this disease with the quality of life of patients becomes an interesting topic to discuss. Besides that quality of life is also a measure of therapeutic success. The better the prognosis of a disease, the better the quality of life, the higher the success rate of therapy (Greimel, 2010).Objective: To know correlation between clinicohistopathological and quality of life in patients with endometrial cancer after undergoing surgery at Sardjito Hospital, Yogyakarta.Method: The research is analytic with cross sectional approach. Patients with endometrial cancer who have undergone total hysterectomy and bisalpingoophorectomy surgery are assessed for their quality of life through interviews and filling out questionnaires in the EORTC QLQ-C 30 and QLQ-EN 24 modules.Results and Discussion: This study, most people with endometrial cancer aged 55-65 years were 34 people (42%) and diagnosed after menopause with a range of age >55 years as many as 43 people (53.1%). This study cannot prove the hypothesis that age, parity, body mass index, type of histopathology and KGB involvement have a relationship with the quality of life of cancer patients (p >0.05). But in contrast to the stage of early cancer (OR 3.17, p=0.044 (CI 95% 1.03-9.75)) and good and moderate differentiation (OR 4.471, p=0.023 (CI 95% 1.23-16.24)) have a significant relationship with quality of life.Conclusion: Clinicohistopathological factors (cancer stage and tumor differentiation) have a correlation with the quality of life at patients with postoperative endometrial cancer in  Sardjito Hospital Keywords: Endometrial cancer; clinicohistopathological factors; quality of life